EXPLORATION OF BANDUNG THROUGH ANHOLT HEXAGONAL CITY BRAND SUSTAINED BY CORN AGRIBUSINESS IN ARJASARI DISTRICT - Beryl Gandakusumah; Rustono Farady Marta (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
West Java as a province with the largest population that oversees many cities, one of which is that Bandung should be able to contribute to the Indonesian economy through the development of aspects of the image of a city which can also be called a city brand. This research will look at the forming components of Bandung, especially the Arjasari region which has not been maximized and can be improved, so as to create a good creative economic development in the Arjasari region and can be socially economically positive for the Arjasari community and the Indonesian people. The research was carried out with a qualitative approach through observations that are analyzed with hexagonal city brand components which are reinforced with literature study data. Through competitive strategies by developing various aspects of forming an area, the Arjasari Region can become a socially advanced region through agricultural products in the form of corn.